Ageing and neurotrophic signalling effects on diaphragm neuromuscular function - Greising, Sarah M (J Physiol, 2015)
The age-related mechanisms underlying sarcopenia are largely unknown. We hypothesize that age-related neuromuscular changes depend on brain-derived neurotrophic factor (BDNF) acting through the tropomyosin-related kinase receptor B (TrkB). Maximal specific force and neuromuscular transmission failure were assessed at 6, 18 and 24 months following control, BDNF or phosphoprotein phosphatase 1 derivative (1NMPP1) treatment in male TrkB(F616A) mice. Phosphoprotein phosphatase-1 derivatives such as 1NMPP1 inhibit TrkB kinase activity as a result of this single amino acid mutation in the ATP binding domain. Maximal twitch and isometric tetanic force were reduced at 24 months compared to 6 and 18 months (P < 0.001). Neuromuscular transmission failure significantly increased at 18 and 24 months compared to 6 months (age × treatment interaction: P < 0.001). Neuromuscular transmission was improved following BDNF at 6 and 18 months and was impaired only at 6 months following 1NMPP1 treatment. Age and inhibition of TrkB kinase activity had similar effects on neuromuscular transmission failure, supporting a critical role for BDNF/TrkB signalling on neuromuscular changes in ageing. These results suggest that an age-related loss of endogenous BDNF precedes reductions in TrkB kinase activity in the diaphragm muscle.